High efficiency perovskite light-emitting diodes of ligand-engineered colloidal formamidinium lead bromide nanoparticles. (August 2017) - Kim, Young-Hoon; Lee, Geon-Hui; Kim, Young-Tae; Wolf, Christoph; Yun, Hyung Joong; Kwon, Woosung; Park, Chan Gyung; Lee, T.-W
Abstract: Formamidinium (FA, CH(NH2 )2 ) lead bromide perovskite (FAPbBr3 ) nanoparticles (NPs) are promising emitters due to their high stability and ability to emit pure green color in both film and solution states. Even though various types of metal halide NP emitters in solution have shown high photoluminescence quantum efficiencies (PLQEs), electroluminescence efficiencies of the light-emitting diodes (LEDs) using the NP films are still much poorer, possibly due to the insulating ligands which can impede the charge injection and transport in films. Therefore, the organic ligand of NPs should be designed to facilitate charge injection and transport in LEDs. Here, we synthesize ligand-engineered colloidal FAPbBr3 NPs at RT and demonstrate high efficiency perovskite NP LEDs based on the FAPbBr3 NPs. Control of ligand length reduces trap-assisted recombination of carriers at the surface traps, and thus maximizes the PLQE of FAPbBr3 NPs. Ligand engineering can also improve the charge injection and transport capability in FAPbBr3 NP films. With this ligand engineering method, we achieve maximum current efficiency of 9.16 cd/A in LEDs based on FAPbBr3 NPs, which is the highest efficiency in FAPbBr3 NP-LEDs to date. The ligand engineering method reported here can be a simple way to improve the luminescence efficiency of optoelectronic devices based on perovskite NP LEDs. Graphical abstract: Highlights: We use ligand engineering to synthesize ligand-engineered colloidal FAPbBr3 nanoparticles (NPs) at RT. Ligand engineering maximizes the luminescence efficiency and the charge injection/transport capability in FAPbBr3 NP film devices. We achieve high efficiency (9.16 cd/A) in light-emitting diodes (LEDs) based on FAPbBr3 NPs.